Synthesis, Radiosynthesis and Biological Evaluation of Buprenorphine-Derived Phenylazocarboxamides as Novel mu-Opioid Receptor Ligands - Krüll, Jasmin; Fehler, Stefanie; Hofmann, Laura; Nebel, Natascha; Maschauer, Simone; Prante, Olaf; Gmeiner, Peter; Lanig, Harald; Hübner, Harald; Heinrich, Markus (ChemMedChem, 2020)
Targeted structural modifications have led to a novel type of buprenorphine-derived opioid receptor ligand displaying an improved selectivity profile for the mu-OR subtype. On this basis, it is shown that phenylazocarboxamides may serve as useful bioisosteric replacements for the widely occurring cinnamide units, without loss of OR binding affinity or subtype selectivity. This study further includes functional experiments pointing to weak partial agonist properties of the novel mu-OR ligands, as well as docking and metabolism experiments. Finally, the unique bifunctional character of phenylazocarboxylates, herein serving as precursors for the azocarboxamide subunit, was exploited to demonstrate the accessibility of an F-18-fluorinated analogue.
Keywords: azo compounds; bioisosters; buprenorphine; opioid receptors; radiosynthesis